Morphological Identification of Major Sponge in Tanjung Senja Water Moramo District, South Konawe Regency - Mangurana, Wa Ode Intiyani; Annastasia, Nurhuda; Patiung, Seventry Meliana; Arsal, La Ode Muh; Wahyudi, Adi Imam (Jurnal Biologi Tropis, 2025)
Sponge organisms are primitive organisms originating from the phylum porifera. These organisms have pores throughout their bodies and have filter feeder properties. Sponges have habitats around coral reef ecosystems, seagrass habitats and in shallow waters. In Tanjung Senja Waters, there are stone mining activities by the community so that research is needed as initial data to determine the types of major sponges in Tanjung Senja waters. On the other hand, apart from being a component of coral reefs, sponges are also natural materials that have the potential to be bioactive compounds that can be developed in the pharmaceutical field. The research was carried out using the free collection method and the sampling point was selected based on the presence of sponges. Water quality parameters were observed in situ or direct observation including temperature, salinity, pH and brightness data.  This study found 3 types of major sponges, namely Callyspongia aerizusa, Stylotella aurantium and Xestospongia sp. This stone mining activity still does not affect the growth of sponges in the waters, this is marked by the results of checking the environmental parameters that have been carried out, it can be concluded that the existence of this sponge is influenced by environmental parameters such as temperature 30oC, current velocity 4.17cm/s, depth 5m, brightness 100%, salinity 33‰ and pH 8, this condition is still at the threshold of quality standards for marine life based on Kep-MENLH No. 51 of 2004.